Incorporation of Ag Nanoparticles Into Micelles. Stability Studies of Self-Organized Nanoparticlesmicelles Structures - Siejak, Przemysław; Polewski, Krzysztof (Current Topics in Biophysics, 2016)
In this paper we present the results of measured physical parameters of self-organized structures consisting of hydrophobic functionalized silver nanoparticles and amphiphilic molecules capable of micelles formation. Those systems may be considered as simple models for transfer of nanoparticles through the biological membrane. Three different surfactants were used: negatively charged sodium dodecyl sulphite, SDS, neutral Triton X-100 and positively charged tetredodecyltrimethyl ammonium bromide, TTABr. We have found that hydrophobic functionalized Ag nanoparticles are encapsulated in neutral Triton X-100 micelles with a diameter of 10 nm without significant change in the size of the micelles. The efficiency of encapsulation of Ag by SDS micelles is lower compared to Triron X-100 and no incorporation of Ag nanoparticles into TTABr occurs. Obtained results indicate that in aqueous environment ionic properties of molecules creating micelles and concentration ratios between components determine the efficiency and kinetics of two competitive processes association or aggregation of nanoparticles and encapsulation of Ag nanoparticles within micelles.